2000
DOI: 10.1111/0008-4085.00055
|View full text |Cite
|
Sign up to set email alerts
|

National borders and international trade: evidence from the European Union

Abstract: In this paper the impact of national borders on international trade within the European Union is considered. Using a gravity model, I find that, averaged over all EU countries, intranational trade is about ten times as high as international trade with an EU partner country of similar size and distance. This relatively strong home bias suggests that even within the European Union national borders still have a decisive impact on trade patterns. JEL Classification: F02, F14, F15, O52Frontières nationales et comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
232
3
19

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(260 citation statements)
references
References 2 publications
6
232
3
19
Order By: Relevance
“…Area π where "Area" represents the size of the prefecture expressed in km 2 . This expression gives the average distance between two points on a circular location (see Crozet, 2004;Mayer, 2000 andNitsch, 2000 for a discussion of this measure of internal distance).…”
Section: Data Source and Construction Of Variablesmentioning
confidence: 99%
“…Area π where "Area" represents the size of the prefecture expressed in km 2 . This expression gives the average distance between two points on a circular location (see Crozet, 2004;Mayer, 2000 andNitsch, 2000 for a discussion of this measure of internal distance).…”
Section: Data Source and Construction Of Variablesmentioning
confidence: 99%
“…The role of a centre can be highlighted or reduced by the weighting of the radius. Nitsch used distance equal to the size of the radiation, which in his opinion is based closely on the value within the average range (Nitsch 2000). Several different approaches can be found in the literature (Rich 1980;Keeble et al 1982;Redding and Venables 2001), but we considered that to be the most appropriate.…”
Section: The Accessibility Model Appliedmentioning
confidence: 99%
“…Instead, we use a remoteness index (REM OT E), which measures the distance between each i country and the rest of the world. It has been constructed following the proposal by Nitsch (2000) and Deardorff (1998), who indicated that the relative distances of trading partners have an impact on the volume of trade and, consequently, remote countries such as Australia and New Zealand can be expected to trade more with each other. 11 The hypothesized sign is that remoteness should not be a priori relevant for cross-border asset trade, since transportation costs for financial assets are zero.…”
Section: On the Determinants Of International Financial Integrationmentioning
confidence: 99%
“…• REM OT E -Remoteness: remoteness is defined following the definition by Nitsch (2000). According to this author, we can define the remoteness of a country i as the reciprocal of country j's GDP divided by the bilateral distance between country i and country j summed over all trading partners of country i (in the sample):…”
Section: Appendix a Data Descriptionmentioning
confidence: 99%